Faktor-Faktor yang Mempengaruhi Tingkat Underpricing: Studi Empiris Perusahaan Keluarga IPO di BEI - Novellia Dwijaya, Hadi Cahyadi (Jurnal Ekonomi, 2021)
This study aims to examine and analyze whether there is a partial or simultaneous influence between firm size, underwriter reputation, firm age, financial leverage, and capital market conditions on the level of underpricing. The population in this study is a family company that has conducted an IPO and has been listed on the Indonesia Stock Exchange for the 2016-2021 period. The method in this research is purposive sampling and the research object used is 45 samples. The results of this study are: company size, underwriter reputation, and company age have a positive and significant effect on the level of underpricing, while financial leverage and capital market conditions have no significant effect on the level of underpricing.Â